(untitled) (Proceedings of International Educators Conference, 2022)
The article considers corpus linguistics technology from the linguodidactic perspective. It focuses on a set of corpora, which might be used in English as a Foreign Language (EFL) teaching: the British National Corpus, the Corpus of Contemporary American English, the Times Magazine Corpus, the Corpus of Historical American English. The paper presents a definition of the instrumental competence as a coherent cluster of knowledge, skills and abilities necessary for the students to use corpus linguistics technology in foreign language learning.